2021
DOI: 10.1101/2021.09.20.21263566
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Health-care workers in gastrointestinal endoscopy are at higher risk for SARS-CoV-2 infection compared to other aerosol-generating disciplines

Abstract: Objective: Healthcare workers (HCW) are at high risk of SARS-CoV-2 infection due to exposure to potentially infectious material, especially during aerosol-generating procedures (AGP). We aimed to investigate the prevalence of infection among HCW in medical disciplines with AGP. Design: A nationwide questionnaire-based study in in- and outpatient settings was conducted between 12/16/2020 and 01/24/2021. Data on SARS-CoV-2 infections among HCW and potential risk factors were investigated. Results: 2,070 healthca… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 27 publications
(27 reference statements)
0
2
0
1
Order By: Relevance
“…As it is a continuation of the CoREM-NUM study, the objective focuses on risk assessment of aerosol-generating procedures in the context of the COVID-19 pandemic. Details and results on the first part of the CoREM-NUM study were reported in previous publications [ 10 , 11 , 12 , 13 ].…”
Section: Methodsmentioning
confidence: 99%
“…As it is a continuation of the CoREM-NUM study, the objective focuses on risk assessment of aerosol-generating procedures in the context of the COVID-19 pandemic. Details and results on the first part of the CoREM-NUM study were reported in previous publications [ 10 , 11 , 12 , 13 ].…”
Section: Methodsmentioning
confidence: 99%
“…SARS-CoV-2 infections among HCWs occurred more often in large practices than in small practices. In both small and large practices, the rate of SARS-CoV-2-positive HCWs was significantly higher than in dental clinics [ 16 ]. Possibly, insufficient pre-interventional testing in practices could have been responsible for this.…”
Section: Discussionmentioning
confidence: 99%
“…Die hier vorgestellten Daten zeigen, dass hierfür jedoch kein Grund besteht: Gegenüber der im gleichen Zeitraum zur Studie angegebenen Infektionsprävalenzrate von 2,6 % in der Gesamtbevölkerung (RKI am 24.01.2021) und einer anzunehmenden Dunkelziffer (von 5,2–7,8 %) sind die berichteten Infektionsraten in deutschen Kliniken und Praxen nicht signifikant höher. Allerdings bilden gastroenterologische Endoskopien an deutschen Kliniken die Ausnahme, denn nach den Augsburger Daten [ 18 , 19 ] lag die Infektionsrate für Personal in gastroenterologischen Kliniken mit 9,9 % signifikant höher als in den anderen untersuchten Einrichtungen des Gesundheitswesens. Daher erscheint es für die nahe Zukunft wichtig, weiterhin möglichst einheitliche, medizinisch effektive Infektionsschutzmaßnahmen besonders in den deutschen Endoskopieeinrichtungen in Kliniken durchzuführen (2- oder 3‑G, ggf.…”
Section: Diskussionunclassified